Evaluating Challenges and Opportunities in the Development and Management of Physical Activity in Albania to Increase the Involvement of the Population in It - Elmazi, Rovena; Junida Pogoni, (European Journal of Multidisciplinary Studies, 2018)
The study aims to assess the challenges, opportunities for development and management of physical activity in Albania compared to other countries in the region. The data collection tool included interviews, and the questionnaire used in all gyms in Albania. The result speaks of a huge gap with regard to the development of sports and the inclusion of populations in physical activities. According to the findings of the study, the number of population frequented by gyms in Albania. It is also worrying the very low number of female participants in the gym compared to the total number of women in the national level and the large difference in the number of males participating in physical activity and mainly in gymnasiums with the number of women that correctly reflected that in Albania it needs the revival and strengthening of gender mechanisms at national and local level. The result also revealed a lack of trained human resources, lack of policies and sound development strategies to increase population participation in physical activities. To this end, the National Sports and Regional Institutions, the Albanian Sports Federation and other relevant sports authorities should take all necessary measures to develop and expand the inclusion of populations into physical activities as a necessary means to increase the quality of life.
Keywords: challenges and opportunities, development, participation policies